Law and Original Contract in the Republican Thought of Immanuel Kant - Vorpagel da Silva, Luciano (Res Publica. Revista de Historia de las Ideas Políticas, 2016)
This article discusses the concept of right and its identification with the power to coerce, to show a reciprocity between the original contract and the right, as a manifestation of the reciprocity between moral law and freedom, as Kant states in its Second Critique. The demonstration of this view will allow a republican stance evident in the legal and political thought of Kant, since the right of a people can only exist while the town itself is unified to enact.
Keywords: Right; power to coerce; external freedom; republicanism; united will of the people.